A SYSTEMATIC APPROACH TO THE STUDY OF CONFLICTS (EDUCATION IN THE 21ST CENTURY, 2023)
parallel with the origin and development of mankind, conflicts and disputes arose and developed. A person throughout his life cannot refrain from conflicts, contradictions, as long as there is development, change, progress. Collisions undoubtedly undermine the natural course of life, human relationships, causing tension, shocks that negatively affect the health of a person, on his mind.Therefore, conflicts at all times were considered by everyone as an undesirable phenomenon. Conflicts, as social phenomena, cover all spheres of life, including the sphere of education, the study and discovery of which is engaged in pedagogical conflictology.In the article, we discussed not only the destructive, but also the constructive meaning of conflict, presenting the manifestations and ways of resolving each period, putting forward the statement that truth is born as a result of disputes, struggles, and the driving force of changes and developments in the world are collisions and contradictions.Studies show that the greatest danger is not the emergence of a conflict, but its mismanagement and put forward solutions. Therefore, the idea that effective conflict management involves identifying the causes of occurrence, preventing the development of destructive conflicts, directing the formation of mainly constructive conflicts and using effective methods and technologies is justified.
Keywords: Conflict, conflict situation, constructive conflict, destructive conflict, conflict of interests, positions, value system, conflict of beliefs, perceptions, conflict.